Influence of the Heredity Kernels on the Prediction of the Life Time of Fiberglass Composites - Olodo, E. T.l; Adjovi, E.C.; Niang, Fadel (My University, 2013)
One of the major problems encountered in the prediction of the hereditary viscoelastic behavior of polymeric composites, is the determination of the heredity kernels. This issue comes down to the identification of the model characterizing the viscoelastic properties of these materials. The purpose of this work is to propose a model for prediction of viscoelastic nonlinear behavior of a composite laminate matrix polyester KACT-B by the study and analysis of the heredity kernels and their influence on the life time of this material. The identification of this model required the experimental determination at room temperature, of the viscoelastic parameters of the heredity kernels by a macroscopic approach. These data provide predictive tools for the establishment of the life time under static complex solicitation and yield strength in the long term for this type of material. Sufficiently interesting in terms of concept and methodology, experimental tests in this study, performed on polymeric fiberglass composite, are still few but develop at a pace that we can look in the near future access suitable for purposes of design data.
Keywords: Heredity kernels; life time; viscoelastic parameters